S"ezd glav gosudarstv SNG . S"ezd glav gosudarstv SNG . Congress of Heads of State of the CIS . Съезд глав государств СНГ - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. The problems of economic integration in the Commonwealth of Independent States (CIS). Проблемы экономической интеграции Содружества Независимых Государств (СНГ).